A New Family of Rigid Dienone Musks Challenges the Perceptive Range of the Human Olfactory Receptor OR5AN1 - Liu, Jie; Hürlimann, Vera; Emter, Roger; Natsch, Andreas; Esposito, Carmen; Linker, Stephanie M.; Zou, Yue; Zhou, Lijun; Wang, Quanrui; Riniker, Sereina; Kraft, Philip (Synlett, 2020)
A new family of dienone musks was discovered by alkylation of different aldehydes with but-3-en-1-yn-1-yllithium and subsequent domino reaction of a Saucy–Marbet transfer vinylation–Claisen rearrangement with an intramolecular Diels–Alder reaction, and concluding Lewis acid catalyzed double-bond isomerization. The newly synthesized dienone structures possess pleasant musk odors displaying fatty, slightly fruity and green facets. Although the dienone musks were predicted in silico to bind to the OR5AN1 receptor based on QM/MM calculations, they were found to be inactive in the in vitro assay. The latter results suggest that the OR5AN1 receptor is not the prime musk receptor but primarily responsible for the animalic character of certain macrocyclic ketones and nitro musks.
Keywords: fragrances; musk odorants; odorant receptors; olfactory properties; structure–activity relationships